Karakteristik Protein Plasma Sapi Bali (CHARACTERISTICS OF BALI CATTLE PLASMA PROTEINS) - Utomo, Wahyu Tri; Suarsana, I Nyoman; Suartini, I Gusti Ayu Agung (Jurnal Veteriner, 2017)
An study was carried out to determine the physiological data on plasma protein characteristics of Bal cattle. A total of 24 plasma samples of male and female bali cattle were characterized by using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS PAGE). The data were presented descriptively. The results showed that on the basis of their estimated molecular weights, at least 14 protein bands (1st to band 14th) were identified with the molecular weights of 963,50 kDa, 530 kDa, kDa 346,82, 124,84 kDa, 89,85 kDa, 68,67 kDa, 54,71 kDa, 37,77 kDa, 20,78 kDa, 16,95 kDa, 16,18 kDa, 15,46 kDa, 12,56 kDa and 10,46 kDa, respectively from the highest to the lowest. Furthermore, plasma protein bands of 14 bali cattle were grouped into five fractions, namely albumin, globulin a1, a2, b, and g. Albumin fraction shown by the band 6th to 14th with a molecular weight of 68,67 to 10,46 kDa respectively. Globulin fraction a1 and a2 shown by the band 5th and 4th with a molecular weight of 89,85 kDa and 124,84 kDa respectively. b- globulin fraction shown by the band 3rd with a molecular weight of 346,82 kDa. g-globulin fraction was shown by the band 1st and 2nd with a molecular weight of 963,50 kDa and 530 kDa respectively. The percentage of area band Bali cattle plasma protein fraction consists of 92% albumin, globulin fraction a2 of 3%, g-globulin of 2%, globulin a1 and b of 1%. It can be concluded that the plasma protein band Bali cattle male and female calves (aged 0-1.5 years), puberty (ages 2-2.5 years) and adults (aged 3-5 years) amounted to 14 protein bands with varying thickness comprises of the five fractions are albumin, globulin a1, a2, b, and g. ABSTRAK Penelitian ini bertujuan untuk mengetahui karakteristik protein plasma sapi bali. Sebanyak 24 sampel plasma sapi bali jantan dan betina dikarakterisasi menggunakan metode sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS PAGE). Data hasil penelitian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa berdasarkan perhitungan bobot molekul pita protein ke-1 sampai pita ke-14 secara berurutan memiliki bobot molekul yaitu 963,50 kDa, 530 kDa, 346,82 kDa, 124,84 kDa, 89,85 kDa, 68,67 kDa, 54,71 kDa, 37,77 kDa, 20,78 kDa, 16,95 kDa, 16,18 kDa, 15,46 kDa, 12,56 kDa, dan 10,46 kDa. Selanjutnya, 14 pita protein plasma sapi bali dikelompokan menjadi lima fraksi yaitu albumin, globulin a1, a2, b, dan g. Fraksi albumin ditunjukan oleh pita ke-6 sampai pita ke-14 dengan bobot molekul 68,67-10,46 kDa. Fraksi globulin a1 dan a2 ditunjukan oleh pita ke-5 dan ke-4 dengan bobot molekul 89,85 kDa dan 124,84 kDa. Fraksi globulin b ditunjukan oleh pita ke-3 dengan bobot molekul 346,82 kDa. Fraksi globulin g ditunjukan oleh pita ke-1 dan ke-2 dengan bobot molekul 963,50 kDa dan 530 kDa. Persentase luas pita protein plasma sapi bali terdiri dari fraksi albumin 92%, fraksi globulin a2 3%, globulin g 2%, globulin a1 dan b 1%. Dapat disimpulkan bahwa pita protein plasma sapi bali jantan dan betina pedet (umur 0-1,5 tahun), pubertas (umur 2-2,5 tahun), dan dewasa (umur 3-5 tahun) berjumlah 14 pita protein dengan ketebalan bervariasi terdiri dari lima fraksi yaitu albumin, globulin a1, a2, a, dan g.